Increasing The Competence of Science Teachers in The Batusangkar City through Technical Guidance on 21st Century Learning Implementation in Integrated Science student worksheet - Ratnawulan - Ratnawulan (Pelita Eksakta, 2022)
One of the problems that often affects the learning process in junior high schools (SMP) is that there are still many science teachers who are not yet skilled in developing thematic Integrated Science Student Worksheets so that the meaning of integration between physics, chemistry, and biology has not been achieved. On the other hand, there needs to be an effort from the teacher, so that students can face the challenges of the 21st century. One of them is by integrating 21st century learning skills into the Student Worksheets used. The purpose of this activity is to improve teacher competence through technical guidance on the implementation of 21st century learning in Integrated Science student worksheets. The form of mentoring activities consists of several stages, namely: orientation, preparation, mentoring 1(in) ; group work. Mentoring 2 (on) in the form of monitoring in partner schools and evaluation. The results achieved from this technical guidance are an increase in the pedagogic and professional competence of teachers from moderate to good.